Qingfei Tongluo Mixture Attenuates Bleomycin-Induced Pulmonary Inflammation and Fibrosis through mTOR-Dependent Autophagy in Rats - Shuyu Ge; Zhenghong Guo; Ting Xiao; Pingping Sun; Bo Yang; Yin Ying (Mediators of Inflammation, 2024)
As an interstitial fibrosis disease characterized by diffuse alveolitis and structural alveolar disorders, idiopathic pulmonary fibrosis (IPF) has high lethality but lacks limited therapeutic drugs. A hospital preparation used for the treatment of viral pneumonia, Qingfei Tongluo mixture (QFTL), is rumored to have protective effects against inflammatory and respiratory disease. This study aims to confirm whether it has a therapeutic effect on bleomycin-induced IPF in rats and to elucidate its mechanism of action. Male SD rats were randomly divided into the following groups: control, model, CQ + QFTL (84 mg/kg chloroquine (CQ) + 3.64 g/kg QFTL), QFTL-L, M, H (3.64, 7.28, and 14.56 g/kg, respectively) and pirfenidone (PFD 420 mg/kg). After induction modeling and drug intervention, blood samples and lung tissue were collected for further detection. Body weight and lung coefficient were examined, combined with hematoxylin and eosin (H&E) and Masson staining to observe lung tissue lesions. The enzyme-linked immunosorbent assay (ELISA) and the hydroxyproline (HYP) assay kit were used to detect changes in proinflammatory factors (transforming growth factor-β (TGF-β), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β)) and HYP. Immunohistochemistry and Western blotting were performed to observe changes in proteins related to pulmonary fibrosis (α-smooth muscle actin (α-SMA) and matrix metalloproteinase 12 (MMP12)) and autophagy (P62 and mechanistic target of rapamycin (mTOR)). Treatment with QFTL significantly improved the adverse effects of bleomycin on body weight, lung coefficient, and pathological changes. Then, QFTL reduced bleomycin-induced increases in proinflammatory mediators and HYP. The expression changes of pulmonary fibrosis and autophagy marker proteins are attenuated by QFTL. Furthermore, the autophagy inhibitor CQ significantly reversed the downward trend in HYP levels and α-SMA protein expression, which QFTL improved in BLM-induced pulmonary fibrosis rats. In conclusion, QFTL could effectively attenuate bleomycin-induced inflammation and pulmonary fibrosis through mTOR-dependent autophagy in rats. Therefore, QFTL has the potential to be an alternative treatment for IPF in clinical practice.